Assessment of Measurement of Salivary Urea by ATR-FTIR Spectroscopy to Screen for CKD. Issue 2 (24th February 2022) - Lin, Tzu-Ling; Evans, Rhys D.R.; Unwin, Robert J.; Norman, Jill T.; Rich, Peter R.
Key Points: Salivary urea can be quantitated rapidly and accurately by infrared spectroscopy in the range relevant to that found in patients with CKD. The measured urea concentrations allowed discrimination of patients with stages 3, 4, or 5 CKD from each other and from healthy controls. This provides a proof of concept that the technique could be developed as a novel, sensitive, and cost-effective screening method for CKD. Abstract : Stages of CKD are currently defined by eGFR and require measurement of serum creatinine concentrations. Previous studies have shown a good correlation between salivary and serum urea levels and the stage of CKD. However, quantitative salivary urea assays in current clinical use require costly and labor-intensive commercial kits, which restricts the advantage of using saliva and limits wider applicability as a quick and easy means of assessing renal function. Attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy has been shown to provide a potentially straightforward, reagent-free method for the identification of a range of disease-related biomarkers and is in current clinical use for analyses of the chemical composition of kidney stones. We assessed the feasibility of ATR-FTIR spectroscopy as an alternative method to measure salivary urea in patients with different stages of CKD. The ATR-FTIR spectra of dried saliva samples from six healthy controls and 20 patients with CKD (stages 1–5) were analyzed to provide their urea concentrations. The lower limit of detection of salivary urea by the ATR-FTIR spectroscopy method was 1–2 mM, at the lower end of the clinically relevant range. Statistically significant differences in salivary urea concentrations were demonstrated between healthy subjects (4.1±0.5 mM) and patients with CKD stages 3–5 (CKD stage 3, 6.8±0.7 mM; CKD stage 4, 9.1±1 mM; CKD stage 5, 14.8±1.6 mM). These salivary urea concentrations correlated well with serum urea levels in the same patients measured by an automated analyzer (Spearman rank correlation coefficient of 0.71; P <0.001). The ability of the method to detect and stage CKD was assessed from the sensitivity and specificity parameters of a receiver operating characteristics (ROC) curve analysis. This proof-of-concept study demonstrates that quantitation of salivary urea by ATR-FTIR spectroscopy could provide a viable tool for rapid and cost-effective diagnosis of stages 3–5 CKD.